(untitled) (American Journal of Islam and Society, 1987)
Introduction Human development, from the Islamic point of view, can be achieved only by following the footsteps of the Prophet (SAAS). The nearer one comes to imbibing the Message of the Quran, Sunnah, and Shari’ah in one’s life, the more humanly developed one becomes, because personal development in Islam is measured by one’s refinement in living this Message. The more refined and developed are the persons in a community, the better will be their culture and civilization. As long as Muslims continued moulding their life according to the Shari‘ah, their civilization in Medina, Baghdad, Andullis, Constantinople, and Delhi flourished. The decline and fall of Islamic civilization came when Muslims started paying mere lip service to the formula of faith and departing from the spirit and purposes of the Shari‘ah. This was the unfortunate phenomenon throughout the Muslim world. Fortunately, the rightly inspired people rose to bring back the erring Muslims to the path of the Shari’ah. This paper seeks to present an assessment of the dynamics used by a Mujaddid (a promoter of Tajdid or revival) of West Africa to re-Islamize a society that had sunk into the abyss of confusion. Islam in West Africa West Africa, situated south of the Sahara desert, and which the Arab historians called Bilad al Sudan, has witnessed in the past, many Islamic empires, e.g., Ghana, Mali, Songhai, and Bornu, the last of which was the Sokoto Caliphate. It emerged from the process of Tajdid (renewal or revival in accordance with the Quran and Sunnah)’ which was started by Shehu (Shaikh) ‘Uthman Danfodio (1754-1817) in 1774, and which culminated in ...